Cytochalasan Alkaloids as TRAIL Sensitizers from an Endophytic Fungus Chaetomium sp. - Gao, Ying; Mao, Ruihua; Liu, Ye; Zhou, Ming; Ruan, Hanli (Planta Medica, 2022)
Two new cytochalasans with a rare 6/6/5/5/7 pentacyclic ring system, named chaetoconvosins C−D (1−2), together with two known congeners (3−4), were isolated from the fermentation of an endophytic fungus, Chaetomium sp. SG-01, harbored in the fibrous roots of Schisandra glaucescens Diels. Their structures including the absolute configuration were elucidated by extensive spectroscopic (HRESIMS, NMR, and ECD) and X-ray crystallographic analyses. The TRAIL-resistance-overcoming activity of 1–4 in a TRAIL-resistant HT29 colorectal cancer cell line was evaluated, which revealed that co-treatment of 1–4 at 50 µM with TRAIL (150 ng/mL) reduced the HT29 cell viability by 19.0%, 24.1%, 17.9%, and 15.5%, respectively, compared to treatment with 1–4 alone.
Keywords: Chaetomiaceae; Chaetomium sp.; cytochalasan alkaloids; cytotoxicity; TRAIL